2009
DOI: 10.4153/cjm-2009-031-6
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic Properties of a Family of Generalized Laguerre Polynomials

Abstract: Abstract. We study the algebraic properties of Generalized Laguerre Polynomials for negative integral values of the parameter. For integers r, n ≥ 0, we conjecture thatis a Q-irreducible polynomial whose Galois group contains the alternating group on n letters. That this is so for r = n was conjectured in the 1950's by Grosswald and proven recently by Filaseta and Trifonov. It follows from recent work of Hajir and Wong that the conjecture is true when r is large with respect to n ≥ 5. Here we verify it in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 4 publications
3
50
0
2
Order By: Relevance
“…In fact the method given by Coleman [2], further developed and refined by Filaseta [4], turns out to be very powerful for studying irreducibility of GLP. The case r = n gives Bessel polynomials and Filaseta and Trifonov [5] proved their irreducibility for all n. It has been proved by Hajir [6] and Sell [9] that L ⟨r ⟩ n (x) is irreducible and its Galois group contains A n when r = 1 or r = 2, respectively. More precisely, Hajir [6] proved that for n ≥ 14,…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact the method given by Coleman [2], further developed and refined by Filaseta [4], turns out to be very powerful for studying irreducibility of GLP. The case r = n gives Bessel polynomials and Filaseta and Trifonov [5] proved their irreducibility for all n. It has been proved by Hajir [6] and Sell [9] that L ⟨r ⟩ n (x) is irreducible and its Galois group contains A n when r = 1 or r = 2, respectively. More precisely, Hajir [6] proved that for n ≥ 14,…”
Section: Introductionmentioning
confidence: 97%
“…For an account of results obtained on GLP, we refer to Hajir [6] and Filaseta [1,4]. We shall restrict α to a negative integer in this paper.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is still an unsolved question whether the Legendre polynomials are irreducible over the rationals, see [23], [24], [30], [40] and [41]. H. Ille has shown that P (0;0) n (x) has no quadratic factors which implies that P (0;0) n p b=c 6 = 0 for all n; b; c 2 N (even for the case b = 1; 3): In passing we note that recent research is devoted to the study of irreducibility of the Laguerre polynomials L n (x) initiated by I. Schur, see [20], [22], [36], and for a family of Jacobi polynomials see [12]. For general questions about irreducibility of polynomial with rational coe¢ cients we refer to [28], [31] and [38].…”
Section: The Main Resultsmentioning
confidence: 99%
“…For applications of Newton's polygon method in the study of the irreducibility for various classes of polynomials, like for instance Bessel polynomials and Laguerre polynomials, we refer the reader to the work of Filaseta [9], [8] [15], [16], [17], and Sell [18].…”
Section: Proof Of the Main Resultsmentioning
confidence: 99%